2018
DOI: 10.1001/jamaneurol.2017.3171
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Oxybate for Excessive Daytime Sleepiness and Sleep Disturbance in Parkinson Disease

Abstract: IMPORTANCE Sleep-wake disorders are a common and debilitating nonmotor manifestation of Parkinson disease (PD), but treatment options are scarce.OBJECTIVE To determine whether nocturnal administration of sodium oxybate, a first-line treatment in narcolepsy, is effective and safe for excessive daytime sleepiness (EDS) and disturbed nighttime sleep in patients with PD. DESIGN, SETTING, AND PARTICIPANTS Randomized, double-blind, placebo-controlled, crossover phase 2a study carried out between January 9, 2015, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 19 publications
0
53
1
Order By: Relevance
“…No significant effects of GHB on functional connectivity were found in the delta, alpha, sigma or beta ranges (results not shown). Clinically, GHB is the first-line treatment of excessive daytime sleepiness and cataplexy in narcolepsy type-1 and has recently been shown to be an effective novel treatment option for sleep-wake disturbances in Parkinson's disease (Büchele et al, 2018;Mamelak, 2018). Although it has been suggested that GHB may augment the regenerative functions of sleep (Mamelak, 2007b(Mamelak, , 2009 and activate similar physiological mechanisms as sleep deprivation (Morawska et al, 2016), the neurophysiological signature of GHB-augmented sleep has not yet been systematically investigated.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…No significant effects of GHB on functional connectivity were found in the delta, alpha, sigma or beta ranges (results not shown). Clinically, GHB is the first-line treatment of excessive daytime sleepiness and cataplexy in narcolepsy type-1 and has recently been shown to be an effective novel treatment option for sleep-wake disturbances in Parkinson's disease (Büchele et al, 2018;Mamelak, 2018). Although it has been suggested that GHB may augment the regenerative functions of sleep (Mamelak, 2007b(Mamelak, , 2009 and activate similar physiological mechanisms as sleep deprivation (Morawska et al, 2016), the neurophysiological signature of GHB-augmented sleep has not yet been systematically investigated.…”
Section: Figurementioning
confidence: 99%
“…Mamelak, 2009). When administered at bedtime, GHB enhances sleep efficiency and electroencephalographic (EEG) slow waves in non rapid eye movement (NREM) sleep, and reduces pathological sleepiness in patients suffering from narcolepsy, Parkinson's disease and fibromyalgia (Huang and Guilleminault, 2009;Ondo et al, 2008;Swick, 2011;Van Cauter et al, 1997;Vienne et al, 2012;Büchele et al, 2018). Given the hypothesized importance of EEG slow waves in NREM sleep for cognition and emotions (Tononi and Cirelli, 2014;Walker, 2009), GHB's beneficial effects have primarily been assigned to its ability to promote slow wave sleep and to produce EEG slow oscillations during sleep (Godbout and Montplaisir, 2002;Morawska et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This study used both objective and subjective assessments and showed that sodium oxybate improved mean sleep latency, ESS score, and slow-wave sleep duration. [ 80 ] Sodium oxybate should be taken in the evening and once again during the night. Its side effects are nausea, insomnia, headache, dizziness, vomiting, weight loss, psychiatric complications, and sleep apnea.…”
Section: Anagement Of E Xcessive mentioning
confidence: 99%
“…[ 81 ] It increased apnea-hypopnea index in PD patients[ 78 ] and induced de novo obstructive sleep apnea and parasomnia. [ 80 ] Efficacy conclusion for sodium oxybate is possibly useful. Evidence suggested that sodium oxybate might be efficacious for treating EDS in PD.…”
Section: Anagement Of E Xcessive mentioning
confidence: 99%
“…Thus, the present study examines self-reported sleep data using the Parkinson's Disease Sleep Scale-Revised [22] to examine whether different aspects of self-reported sleep problems are differentially associated with memory and executive function (EF) in younger versus older-onset PD. Variants of the Parkinson's Disease Sleep Scales (PDSS [23]; PDSS-2 [24]) have been widely adopted by clinicians and integrated as outcome measures in clinical trials [25][26][27], therefore, understanding systematic differences in the antecedents and associations of sleep disturbances within PD subtype is critical.…”
Section: Introductionmentioning
confidence: 99%